A polymer waterproof material and slope protection waterproof isolation pad
By using polymer waterproofing materials and modified mixed soil compositions in the landfill, a slope protection waterproof isolation pad with good anti-seepage effect is formed, which solves the problem of failure of the protection function of garbage leachate in the prior art and improves environmental safety properties and durability of materials.
Patent Information
- Application Number
- CN202311185713.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-14
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2043-09-14
AI Technical Summary
The compacted clay, bentonite waterproof blankets and geomembranes used in existing landfills are prone to failure in the protection function of garbage leachate, resulting in pollutant leakage and affecting environmental safety.
A polymer waterproof material is used to react homogeneously under ultraviolet radiation conditions through raw materials such as ethylene glycol dimethacrylate and glycidyl methacrylate to form a modifier and with diethyl triamine and butyl The reaction of diacid anhydride and other reactions is made to prepare polymer polymers, and combined with the modified mixed soil composition, a slope protection and waterproof isolation pad with good anti-seepage effect is formed.
Improve the anti-seepage effect of garbage leachate, enhance the water resistance, shear strength and durability of the material, reduce the permeability and water absorption rate, effectively prevent the leakage of pollutants in garbage leachate, and improve the landfill Environmental safety.
Smart Images

Figure CN117264219B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a polymer waterproof material and a slope protection waterproof isolation pad. Background Art
[0002] Garbage disposal methods can generally be divided into several methods such as sanitary landfill, incineration, and composting. Landfill accounts for more than 80% of the amount of urban waste disposal and is currently the main method for disposing urban solid waste in my country. Leachate refers to the sewage formed by leaching due to the decomposition of organic matter in the garbage and the free water in the garbage, precipitation, and infiltrated groundwater during the landfill and stacking process. The infiltration of leachate pollutes the surrounding soil and groundwater, posing a potential threat to environmental safety. Landfills often use waterproof isolation pads composed of geomembranes and compacted clay liners or geocomposite bentonite pads to prevent pollution of leachate. The liner system is the most critical part of all landfill systems. At present, the commonly used liner materials at home and abroad include compacted clay, bentonite waterproof blankets, geomembranes, etc. The permeability of clay soil is related to many factors, such as temperature, cracks, deformation, density, etc. The effect of leachate will affect the mechanical properties and permeability properties of the clay liner in the landfill. Under the long-term influence of high temperature in the landfill, the engineering properties of the bottom liner material change, causing changes in the exchange and adsorption capacity of ions on the clay surface, soil permeability, deformation and strength, resulting in engineering problems such as landfill liner settlement, decreased stability, and leachate leakage, leading to failure of the liner system and contamination of the surrounding soil and groundwater, posing a potential threat to environmental safety.
[0003] In a complex environment, leachate and the trace pollutants it carries can easily penetrate the landfill anti-pollution barrier, especially through the weak links of the barrier to produce a dominant flow, and penetrate and diffuse into the underground environment, causing urban underground environmental pollution disasters. The concentration of leachate pollutants is hundreds of times that of urban sewage, and the pollution lasts for decades or even hundreds of years, making pollution remediation extremely difficult. The leachate from the landfill corrodes and destroys the soil particles in the liner material, causing particle reorganization, increasing the gaps between particles, increasing the surface smoothness, and reducing the compactness of the structure; in addition, after being corroded by the leachate, the attraction between the soil particles disappears, the bonding force between the particles is destroyed, making it looser, and after the liner is squeezed laterally, the relative activity between the soil particles increases, the ability to resist deformation decreases, and the shear strength also decreases, and the anti-seepage effect of the liner material is greatly reduced. Summary of the invention
[0004] The purpose of the present invention is to provide a polymer waterproof material and a slope protection waterproof isolation pad to solve the following technical problems:
[0005] The existing slope protection waterproof isolation pads used in landfills to protect against landfill leachate are a combination of compacted clay, bentonite waterproof blankets, and geomembranes. The anti-seepage function is easily ineffective, resulting in the leakage of pollutants.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A polymer waterproof material, comprising the following raw materials in parts by weight: 1 part by weight of a modifier, 3-10 parts by weight of a polymer;
[0008] The preparation method of the modifier comprises the following steps: adding ethylene glycol dimethacrylate, glycidyl methacrylate and polyethylene glycol into a reaction kettle A, adding benzoin dimethyl ether, dispersing evenly, treating with ultraviolet radiation, extracting in a Soxhlet extractor with methanol as solvent, and vacuum drying to obtain the modifier;
[0009] The preparation method of the high molecular polymer comprises the following steps:
[0010] S1: Add succinic anhydride and diethyltriamine to reaction bottle A and disperse them evenly. Heat to 100-130°C under vacuum conditions and keep warm for 1-3 hours. Heat to 150-170°C and keep warm for 1-3 hours. Add methanol and disperse them evenly. Reprecipitate with acetone, filter, wash and dry to obtain component 1.
[0011] S2: Add component 1 and anhydrous methanol into reaction bottle B, disperse evenly, heat to 70-80°C, add benzaldehyde, keep warm for 3-6 hours, filter and dry to obtain component 2;
[0012] S3: Add component 2, N,N-dimethylacetamide and chloroform into reactor B, disperse evenly, let stand at room temperature for 9-12 hours, add 1,2,4-trimellitic anhydride chloride and disperse evenly, continue to add SnCl4, stir for 3-6 hours at room temperature, filter, wash with water and dry to obtain a high molecular polymer.
[0013] As a further solution of the present invention: the ultraviolet radiation treatment is specifically: exposure at 20-30 cm under a 1000W ultraviolet lamp for 1-10 minutes.
[0014] As a further solution of the present invention: the mass ratio of ethylene glycol dimethacrylate, glycidyl methacrylate, polyethylene glycol and benzoin dimethyl ether is 1:1.5-3:5-10:0.5-2.
[0015] As a further embodiment of the present invention: the mass ratio of succinic anhydride, diethyltriamine and methanol in S1 is 1:1-2:5-10.
[0016] As a further solution of the present invention: the mass ratio of component 1, anhydrous methanol and benzaldehyde in S2 is 1:5-10:0.2-0.5.
[0017] As a further solution of the present invention: the addition ratio of component 2, N,N-dimethylacetamide, chloroform, 1,2,4-trimellitic anhydride chloride, and SnCl4 in S3 is 1g:30-100mL:20-50mL:1-5g:1-2mL.
[0018] As a further solution of the present invention: the preparation method of the polymer waterproof material comprises the following steps: mixing the modifier, the solvent and the polymer, reacting for 12-24 hours under stirring conditions at room temperature, washing and drying to obtain the polymer waterproof material.
[0019] As a further solution of the present invention: the mass ratio of the modifier, the solvent and the high molecular polymer is 1:300-500:3-10, and the solvent is acetone.
[0020] The slope protection waterproof isolation pad comprises an upper geotextile, a lower geotextile and a modified mixed soil composition sandwiched therein, wherein the modified mixed soil composition comprises modified mixed soil and any of the above-mentioned polymer waterproof materials.
[0021] As a further solution of the present invention: the upper geotextile and the lower geotextile are knitted, sewn or bonded into a hollow bag-like structure.
[0022] As a further scheme of the present invention: the preparation method of the modified mixed soil comprises the following steps: after the calcium-based bentonite and deionized water are mixed evenly, tetraethylene pentamine is added, stirring is carried out at room temperature for 1-2 hours, filtering, washing with water until neutral, adding clay, stirring evenly, and obtaining the modified mixed soil; the mass ratio of the calcium-based bentonite, deionized water, tetraethylene pentamine, and clay is 1:10-50:0.1-0.5:8-15.
[0023] As a further solution of the present invention: the modified mixed soil composition is prepared by mixing modified mixed soil and polymer waterproof material in a mass ratio of 10:0.5-2.
[0024] As a further solution of the present invention: the clay particle size includes the following mass percentages: 40-50% 0-0.075mm, 30-40% 0.075-0.25mm, 2-5% 0.25-0.5mm, 0.5-2mm remainder, and the sum of each component is 100%.
[0025] As a further embodiment of the present invention, the bentonite particle size comprises the following mass percentages: 40-60% 0-0.075 mm, 20-40% 0.075-0.25 mm, 1-3% 0.25-0.5 mm, and 0.5-2 mm remainder, and the sum of each component is 100%.
[0026] Beneficial effects of the present invention:
[0027] (1) This application first uses ethylene glycol dimethacrylate and glycidyl methacrylate as raw materials and polyethylene glycol as a porogen. In a homogeneous reaction system and under ultraviolet radiation conditions, benzoin dimethyl ether decomposes to induce a polymerization reaction, and is connected to each other through chemical bonds to form a porous polymer containing epoxy groups to obtain a modifier; this application adopts a divergent method to use diethyltriamine as a core and reacts with succinic anhydride to obtain a polymer with a carboxyl terminal group, namely component one; and uses benzaldehyde to modify component one to obtain component two; and then uses the benzene ring of component two to react with 1,2,4-trimellitic anhydride chloride to obtain a high molecular polymer under the catalysis of SnCl4. Finally, the secondary amine on the high molecular polymer prepared by this application undergoes alkylation with the epoxy group on the modifier to obtain a high molecular waterproof material. The present application performs terminal modification on component one by grafting benzene rings, thereby increasing the pressure resistance and thermal stability of the high molecular polymer, and having the characteristics of good chemical stability and resistance to organic solvents. When added to the modified mixed soil composition, the high molecular polymer prepared by the present application decreases in permeability under the action of active chlorine and the like in the leachate when preventing the seepage of garbage leachate, and the strong hydrogen bonding between the rigid aromatic ring and the amide bond restricts the internal chain activity of the polymer, resulting in a small free volume, thereby increasing the anti-seepage effect of the material. The present application's component one is modified with benzaldehyde and 1,2,4-trimellitic anhydride in turn to obtain a high molecular polymer, which solves the problem of directly adding component one and causing the rich amide groups in component one to result in high water absorption, low heat deformation temperature and low strength of the material. The polymer waterproof material prepared in the present application has cationic properties and active side chains. When added to soil particles, it gives the material good water resistance. The polymer reacts with the amino groups grafted on the surface of the soil particles to form a cross-linked network structure, which effectively improves the wet strength and water resistance of the material. The polymer waterproof material prepared in the present application contains active groups such as tertiary amines and quaternary ammonium functional groups and porous structures of various sizes, which improve the anti-seepage and adsorption capacity of the liner, have a high specific surface area and ion exchange capacity, have a high adsorption capacity for heavy metal ions, and the anti-seepage effect of the slope protection waterproof isolation pad on garbage leachate is enhanced.
[0028] (2) The upper and lower layers of geotextiles of the slope protection waterproof isolation mat prepared in this application play a protective and reinforcing role, giving the slope protection waterproof isolation mat a certain overall shear strength and tensile strength. The modified mixed soil composition sandwiched in the middle includes modified mixed soil and polymer waterproof materials. The modified mixed soil contains clay and bentonite. This application uses appropriate grading of clay and bentonite to make the material have the advantages of high dry density, small intergranular pores and low permeability after compaction. Among them, bentonite itself has strong hygroscopic expansion and high cation exchange capacity, and low water permeability when wet. After bentonite absorbs water, its volume can expand to 10-30 times its original volume, and low permeability fibers will be formed inside it. Therefore, after adding an appropriate amount of bentonite to clay, it can not only reduce the porosity of the clay, thereby reducing its permeability coefficient, but also improve the adsorption capacity and mechanical strength of the anti-seepage lining layer. The present application adds polymer waterproof materials to the modified mixed soil, which effectively avoids the problem that bentonite is added to clay, causing the mixed soil to be prone to cracks due to drying, freeze-thaw, etc., which in turn causes the cracks to provide advantageous leakage channels for water and leachate, causing the material to lose its anti-seepage ability; and improves the durability of the modified mixed soil composition in the slope protection waterproof isolation pad.
[0029] (3) The present application adds polymer waterproof materials to the modified mixed soil prepared by mixing clay and bentonite, which gives the slope protection waterproof isolation pad certain chemical corrosion resistance, tear resistance and penetration resistance, as well as durability and firmness. The polymer waterproof material prepared in the present application is added to the modified mixed soil, and the polymer waterproof material and the modified mixed soil are cross-linked with each other by chemical bonds, which limits the mutual sliding of the materials, improves the mutual bite between the soil particles in the modified mixed soil composition, reduces the relative activity between the particles, and improves the internal cohesion and internal friction angle of the material; the electrostatic force, van der Waals force and cementation between the soil particles and the polymer waterproof material themselves and each other improve the cohesion of the material, thereby achieving the effect of improving the shear strength of the material.
[0030] (4) The polymer waterproof material prepared in this application is added to the modified mixed soil to modify the material's adsorption and hydrophobicity. The polymer waterproof material is inserted into the intercrystalline layers of soil particles through cation exchange to form a dense hydrophobic monomolecular polymer layer, which excludes interlayer water molecules. The hydration dispersion and swelling degree of soil particles are effectively controlled, and the size of clay particles becomes larger, effectively reducing the displacement of organic solvents and cations in the landfill leachate on the adsorbed water on the soil particles and the cation exchange, which causes the clay volume to change, and the acid and alkali in the leachate dissolve some soil particles. The modified mixed soil composition prepared in this application has the characteristics of high adsorption rate, fast adsorption rate, and selective adsorption, which effectively avoids the problem that after the soil particles are corroded by landfill leachate, the pores between the particles increase, resulting in reduced structural compactness and reduced attraction between particles. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The present invention will be further described below in conjunction with the accompanying drawings.
[0032] Figure 1 It is a cross-sectional schematic diagram of a slope protection waterproof isolation pad;
[0033] In the figure: 1. upper geotextile; 2. lower geotextile; 3. modified mixed soil composition. DETAILED DESCRIPTION
[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] Example 1
[0036] The preparation method of the modifier comprises the following steps:
[0037] 10g of ethylene glycol dimethacrylate, 20g of glycidyl methacrylate and 60g of PEG2000 were added into reactor A, and 10g of benzoin dimethyl ether was added and dispersed evenly. The mixture was exposed to light at 30cm under a 1000W ultraviolet lamp for 10min. The mixture was extracted in a Soxhlet extractor with methanol as solvent and dried under vacuum to obtain a modifier.
[0038] Example 2
[0039] The method for preparing the high molecular weight polymer comprises the following steps:
[0040] S1: Add 50g of succinic anhydride and 50g of diethyltriamine into reaction bottle A and disperse them evenly. Heat to 100℃ under vacuum and keep warm for 1h. Heat to 150℃ and keep warm for 1h. Add 250g of methanol and disperse them evenly. Reprecipitate with acetone, filter, wash and dry to obtain component 1.
[0041] S2: Add 100g of component 1 and 500g of anhydrous methanol into a reaction bottle, disperse evenly, heat to 70°C, add 20g of benzaldehyde, keep warm for 3h, filter and dry to obtain component 2;
[0042] S3: Add 100g of component 2, 3000mL of N,N-dimethylacetamide and 2000mL of chloroform into reactor B, disperse evenly, let stand at room temperature for 9h, add 100g of 1,2,4-trimellitic anhydride chloride and disperse evenly, continue to add 100mL of SnCl4, stir at room temperature for 3h, filter, wash with water and dry to obtain a high molecular polymer.
[0043] Example 3
[0044] The method for preparing the high molecular weight polymer comprises the following steps:
[0045] S1: Add 50g of succinic anhydride and 70g of diethyltriamine into reaction bottle A and disperse them evenly. Heat to 120℃ under vacuum and keep warm for 2h. Heat to 160℃ and keep warm for 2h. Add 400g of methanol and disperse them evenly. Reprecipitate with acetone, filter, wash and dry to obtain component 1.
[0046] S2: Add 100g of component 1 and 700g of anhydrous methanol into a reaction bottle, disperse evenly, heat to 75°C, add 40g of benzaldehyde, keep warm for 5h, filter and dry to obtain component 2;
[0047] S3: Add 100g of component 2, 7000mL of N,N-dimethylacetamide and 4000mL of chloroform into reactor B, disperse evenly, let stand at room temperature for 10h, add 300g of 1,2,4-trimellitic anhydride chloride and disperse evenly, continue to add 150mL of SnCl4, stir for 3h at room temperature, filter, wash with water and dry to obtain a high molecular polymer.
[0048] Example 4
[0049] The method for preparing the high molecular weight polymer comprises the following steps:
[0050] S1: Add 50g of succinic anhydride and 100g of diethyltriamine into reaction bottle A and disperse them evenly. Heat to 130℃ under vacuum and keep warm for 3h. Heat to 170℃ and keep warm for 3h. Add 500g of methanol and disperse them evenly. Reprecipitate with acetone, filter, wash and dry to obtain component 1.
[0051] S2: Add 100g of component 1 and 1000g of anhydrous methanol into a reaction bottle, disperse evenly, heat to 80°C, add 50g of benzaldehyde, keep warm for 6h, filter and dry to obtain component 2;
[0052] S3: Add 100g of component 2, 10000mL of N,N-dimethylacetamide and 5000mL of chloroform into reactor B, disperse evenly, let stand at room temperature for 12h, add 500g of 1,2,4-trimellitic anhydride chloride and disperse evenly, continue to add 200mL of SnCl4, stir at room temperature for 6h, filter, wash with water and dry to obtain a high molecular polymer.
[0053] Example 5
[0054] The preparation method of the polymer waterproof material comprises the following steps:
[0055] 10 g of the modifier prepared in Example 1, 3000 g of acetone, and 50 g of the high molecular polymer prepared in Example 2 were mixed, reacted under stirring at room temperature for 24 hours, washed, and dried to obtain a high molecular waterproof material.
[0056] Example 6
[0057] The preparation method of the polymer waterproof material comprises the following steps:
[0058] 10 g of the modifier prepared in Example 1, 3000 g of acetone, and 50 g of the high molecular polymer prepared in Example 3 were mixed, reacted under stirring at room temperature for 24 hours, washed, and dried to obtain a high molecular waterproof material.
[0059] Example 7
[0060] The preparation method of the polymer waterproof material comprises the following steps:
[0061] 10 g of the modifier prepared in Example 1, 3000 g of acetone, and 50 g of the high molecular polymer prepared in Example 4 were mixed, reacted under stirring at room temperature for 24 hours, washed, and dried to obtain a high molecular waterproof material.
[0062] Example 8
[0063] The preparation method of the polymer waterproof material comprises the following steps:
[0064] 10 g of the modifier prepared in Example 1, 3000 g of acetone and 30 g of the high molecular polymer prepared in Example 2 were mixed, reacted under stirring at room temperature for 24 h, washed and dried to obtain a high molecular waterproof material.
[0065] Example 9
[0066] The preparation method of the polymer waterproof material comprises the following steps:
[0067] 10 g of the modifier prepared in Example 1, 3000 g of acetone, and 100 g of the high molecular polymer prepared in Example 2 were mixed, reacted under stirring at room temperature for 24 h, washed, and dried to obtain a high molecular waterproof material.
[0068] Example 10
[0069] See also Figure 1 , the slope protection waterproof isolation pad includes the following structures:
[0070] B1: The clay particle sizes include the following mass percentages: 50% 0-0.075mm, 40% 0.075-0.25mm, 5% 0.25-0.5mm, 5% 0.5-2mm; the bentonite particle sizes include the following mass percentages: 60% 0-0.075mm, 35% 0.075-0.25mm, 3% 0.25-0.5mm, 2% 0.5-2mm;
[0071] B2: The preparation method of the modified mixed soil comprises the following steps: 50g of calcium bentonite and 500mL of deionized water are mixed evenly, 5g of tetraethylenepentamine is added, stirred at room temperature for 1h, filtered, washed with water until neutral, 500g of clay is added, and stirred evenly to obtain a modified mixed soil;
[0072] B3: 500 g of the modified mixed soil and 50 g of the polymer waterproof material prepared in Example 5 were mixed to prepare a modified mixed soil composition 3;
[0073] B4: The upper geotextile 1 and the lower geotextile 2 are knitted into a hollow bag-like structure, and the modified mixed soil composition 3 prepared above is sandwiched therein.
[0074] Embodiment 11
[0075] Compared with Example 10, Example 11 only replaces an equal amount of the polymer waterproof material prepared in Example 5 with the polymer waterproof material prepared in Example 6, and the other components and steps are exactly the same as Example 10.
[0076] Example 12
[0077] Compared with Example 10, Example 11 only replaces an equal amount of the polymer waterproof material prepared in Example 5 with the polymer waterproof material prepared in Example 7, and the other components and steps are exactly the same as Example 10.
[0078] Embodiment 13
[0079] Compared with Example 10, Example 11 only replaces an equal amount of the polymer waterproof material prepared in Example 5 with the polymer waterproof material prepared in Example 8, and the other components and steps are exactly the same as Example 10.
[0080] Embodiment 14
[0081] Compared with Example 10, Example 11 only replaces an equal amount of the polymer waterproof material prepared in Example 5 with the polymer waterproof material prepared in Example 9, and the other components and steps are exactly the same as Example 10.
[0082] Embodiment 15
[0083] Compared with Example 10, Example 11 only replaces 50g of the polymer waterproof material prepared in Example 5 with 25g of the polymer waterproof material prepared in Example 5, and the other components and steps are exactly the same as those of Example 10.
[0084] Example 16
[0085] Compared with Example 10, Example 11 only replaces 50g of the polymer waterproof material prepared in Example 5 with 100g of the polymer waterproof material prepared in Example 5, and the other components and steps are exactly the same as those of Example 10.
[0086] Comparative Example 1
[0087] The method for preparing the high molecular weight polymer comprises the following steps:
[0088] S1: Add 50g of succinic anhydride and 50g of diethyltriamine into reaction bottle A and disperse them evenly. Heat to 100℃ under vacuum condition and keep warm for 1h. Heat to 150℃ and keep warm for 1h. Add 250g of methanol and disperse them evenly. Reprecipitate with acetone, filter, wash and dry to obtain a high molecular polymer.
[0089] Comparative Example 2
[0090] The method for preparing the high molecular weight polymer comprises the following steps:
[0091] S1: Add 50g of succinic anhydride and 50g of diethyltriamine into reaction bottle A and disperse them evenly. Heat to 100℃ under vacuum and keep warm for 1h. Heat to 150℃ and keep warm for 1h. Add 250g of methanol and disperse them evenly. Reprecipitate with acetone, filter, wash and dry to obtain component 1.
[0092] S2: Add 100g of component 1 and 500g of anhydrous methanol into a reaction bottle, disperse them evenly, heat to 70°C, add 20g of benzaldehyde, keep the temperature to react for 3h, filter and dry to obtain a high molecular polymer.
[0093] Comparative Example 3
[0094] The preparation method of the polymer waterproof material comprises the following steps:
[0095] Compared with Example 5, in Comparative Example 3, only an equal amount of the high molecular weight polymer prepared in Example 2 added therein is replaced with the high molecular weight polymer prepared in Comparative Example 1, and the other components and steps are completely consistent with Example 5.
[0096] Comparative Example 4
[0097] The preparation method of the polymer waterproof material comprises the following steps:
[0098] Compared with Example 5, in Comparative Example 4, only an equal amount of the high molecular weight polymer prepared in Example 2 added therein is replaced with the high molecular weight polymer prepared in Comparative Example 2, and the other components and steps are completely consistent with Example 5.
[0099] Comparative Example 5
[0100] Compared with Example 10, in Comparative Example 5, only the polymer waterproof material prepared in Example 5 is replaced by an equal amount of the polymer waterproof material prepared in Comparative Example 3, and the other components and steps are exactly the same as those in Example 10.
[0101] Comparative Example 6
[0102] Compared with Example 10, in Comparative Example 6, only the polymer waterproof material prepared in Example 5 added therein is replaced with an equal amount of the polymer waterproof material prepared in Comparative Example 4, and the other components and steps are completely consistent with Example 10.
[0103] Comparative Example 7
[0104] Compared with Example 10, in Comparative Example 7, only an equal amount of the high molecular waterproof material prepared in Example 5 added therein is replaced with the high molecular polymer prepared in Example 2, and the other components and steps are completely consistent with Example 10.
[0105] Comparative Example 8
[0106] The slope protection waterproof isolation pad includes the following structures:
[0107] B1: The clay particle sizes include the following mass percentages: 50% 0-0.075mm, 40% 0.075-0.25mm, 5% 0.25-0.5mm, 5% 0.5-2mm; the bentonite particle sizes include the following mass percentages: 60% 0-0.075mm, 35% 0.075-0.25mm, 3% 0.25-0.5mm, 2% 0.5-2mm;
[0108] B2: Mix 50g of calcium bentonite and 500g of clay to obtain a mixed soil;
[0109] B3: 500 g of mixed soil and 50 g of the polymer waterproof material prepared in Example 5 were mixed to obtain a modified mixed soil composition 3;
[0110] B4: The upper geotextile 1 and the lower geotextile 2 are knitted into a hollow bag-like structure, and the modified mixed soil composition 3 prepared above is sandwiched therein.
[0111] Comparative Example 9
[0112] The slope protection waterproof isolation pad includes the following structures:
[0113] B1: Clay particle sizes include the following mass percentages: 50% 0-0.075mm, 40% 0.075-0.25mm, 5% 0.25-0.5mm, 5% 0.5-2mm;
[0114] B2: After 50g of clay and 500mL of deionized water were mixed evenly, 5g of tetraethylenepentamine was added, stirred at room temperature for 1h, filtered, and washed with water until neutral to obtain modified clay;
[0115] B3: 500 g of modified clay and 50 g of the polymer waterproof material prepared in Example 5 were mixed to prepare a modified mixed soil composition 3;
[0116] B4: The upper geotextile 1 and the lower geotextile 2 are knitted into a hollow bag-like structure, and the modified mixed soil composition 3 prepared above is sandwiched therein.
[0117] Comparative Example 10
[0118] The slope protection waterproof isolation pad includes the following structures:
[0119] B1: The clay particle sizes include the following mass percentages: 50% 0-0.075mm, 40% 0.075-0.25mm, 5% 0.25-0.5mm, 5% 0.5-2mm; the bentonite particle sizes include the following mass percentages: 60% 0-0.075mm, 35% 0.075-0.25mm, 3% 0.25-0.5mm, 2% 0.5-2mm;
[0120] B2: 50 g of calcium bentonite and 500 g of clay were mixed evenly to obtain a modified mixed soil composition 3;
[0121] B3: The upper geotextile 1 and the lower geotextile 2 are knitted into a hollow bag-like structure, and the modified mixed soil composition 3 prepared above is sandwiched therein.
[0122] Performance Testing
[0123] (1) The physical and chemical properties of the clay and bentonite used in this application were tested. The test results are shown in Table 1-2;
[0124] Table 1: Statistical table of physical properties of clay and bentonite
[0125]
[0126] Table 2: Statistical table of chemical properties of clay and bentonite
[0127]
[0128] (2) Crack parameters
[0129] a: Operation steps:
[0130] In a container with a plane size of 30cmx40cm, the modified mixed soil composition of Example 10 and Comparative Example 10 and clay were placed in the container respectively and compacted (the soil sample thickness is 3cm), (compacting power: 2.5kg drop hammer, 46cm drop distance, 25 hits per layer). The dehumidification process of the soil was simulated by artificial drying method (50°C). The soil was subjected to two dry-wet cycles, specifically: first, the soil was dehumidified to a moisture content of 5%, then humidified to a moisture content of 25%, and then dehumidified to a moisture content of 5%; during the drying process, the surface of the soil sample was photographed and weighed at regular intervals;
[0131] b: Processing data:
[0132] ① Binarize the image, represent the crack part in black and the rest in white, and the ratio of the crack area to the total area of the soil sample is the crack area rate;
[0133] ② Vectorize the binary image to obtain the centerline vector diagram and the total length of the crack;
[0134] ③ The ratio of the total length of the crack to the area of the soil sample is the length ratio of the crack, and the ratio of the crack area to the crack length is the average width of the crack; the test results are shown in Table 3;
[0135] Table 3: Statistical table of Example 10, Comparative Example 10 and clay crack parameters
[0136]
[0137] As shown in Table 3, the polymer waterproof material prepared in the present application is added to the modified mixed soil, which effectively reduces the problem that the addition of bentonite to clay causes the mixed soil to crack due to drying, freezing and thawing, and then causes the cracks to provide advantageous leakage channels for water and leachate, causing the material to lose its anti-seepage ability. Improve the durability of the modified mixed soil composition in the slope protection waterproof isolation mat.
[0138] (3) Filtration performance
[0139] a: Collecting leachate: Collect leachate from garbage dumps in suburban areas and test the physical and chemical properties of the initial leachate;
[0140] b: Permeability coefficient: According to GB / T 16889-2008, the variable head permeability test method was carried out using the ST-55 improved permeameter (the variable head device uses a glass tube with an inner diameter of 0.7 cm and a length of 165.8 cm); firstly, the standard light compaction instrument was used for compaction (compaction power: drop hammer 2.5 kg, drop distance 46 cm, 25 hits per layer), and then the ring knife was used for sampling and then the air saturation test was carried out, and then the variable head permeability test was carried out to determine the saturated permeability coefficient;
[0141] During the test, the outlet water temperature was recorded and the permeability coefficient KT at the actual temperature was calculated using the following formula:
[0142] KT=2.3[aL / A(t2-t1)]lg(h1 / h2)
[0143] Where, KT-permeability coefficient at actual temperature, cm / s; a-cross-sectional area of variable head pipe, cm 2 ; L-diameter, i.e. the height of the sample, cm; A-cross-sectional area of the sample, cm 2 ; t1-start time of measuring water head, s; t2-end time of measuring water head, s; h1-start water head in the pressure measuring tube, cm; h2-end water head in the pressure measuring tube, cm; 2.3-conversion factor of ln and lg;
[0144] K20=KT (ηT / η20)
[0145] Where: K20-permeability coefficient of the sample when the water temperature is 20℃, cm / s; ηT-dynamic viscosity coefficient of water at T℃, kPa·s; η20-dynamic viscosity coefficient of water at 20℃, kPa·s; the test results are shown in Table 4;
[0146] c: Retardation rate: Collect the infiltrated garbage leachate obtained in step b, detect the physical and chemical properties of the treated garbage leachate, and calculate the retardation rate η of each substance in the garbage leachate. The calculation of the retardation rate η is shown in the following formula:
[0147] η=[(C0-C1) / C0]×100%
[0148] Wherein, η-blocking rate, %; C0-initial value of relevant data of landfill leachate, mg / L; C1-value of relevant data after landfill leachate penetration test, mg / L; the test results are shown in Table 4;
[0149] Table 4: Statistical table of percolation performance test data of Examples 10-16 and Comparative Examples 5-10
[0150]
[0151] It can be seen from Table 4 that the modified mixed soil composition prepared by adding the polymer waterproof material prepared in the present application to the modified mixed soil has excellent anti-seepage effect on landfill leachate, and has good anti-seepage adsorption effect on heavy metal ions, ammonia nitrogen compounds and other substances in the landfill leachate. After long-term use, it still maintains excellent anti-seepage filtration performance for landfill leachate.
[0152] (4) Shear strength
[0153] a: According to the Geotechnical Test Regulations, the maximum dry density of clay is 1.631 g / cm 3 , the optimal moisture content is 22.4%;
[0154] b: The modified mixed soil compositions prepared in Examples 10-16 and Comparative Examples 5-10 were air-dried, crushed, passed through a 2mm sieve, and dried in an oven. According to the optimum moisture content and maximum dry density of the clay, the modified mixed soil compositions prepared in Examples 10-16 and Comparative Examples 5-10 were cut into a ring with a diameter of 61.8mm and a height of 20mm. A shear test was performed using a ZJ strain-controlled direct shear apparatus (Nanjing Ningxi Soil Instrument Co., Ltd.) to determine the shear strength variation of the soil samples under vertical pressures of 100, 200, 300, and 400kPa. After applying the vertical pressure, the vertical deformation was measured every 1h. When the consolidation deformation was no greater than 0.005mm / h, the consolidation deformation of the sample was considered stable. The shear load was applied at a rate of 0.8mm / min, and the force gauge reading was recorded. If the force gauge reading reached stability or retreated significantly, it indicated that the sample had been sheared and damaged, and the peak value was taken as the shear strength value. If the dynamometer reading continues to increase, the test is stopped when the shear deformation reaches 6 mm, and the shear stress corresponding to the shear strain of 4 mm is taken as the shear strength P0. The test results are shown in Table 5;
[0155] c: The modified mixed soil compositions prepared in Examples 10-16 and Comparative Examples 5-10 were air-dried, crushed, passed through a 2 mm sieve, and dried in an oven. According to the optimum moisture content and maximum dry density of the clay, the modified mixed soil compositions prepared in Examples 10-16 and Comparative Examples 5-10 were cut into a ring with a diameter of 61.8 mm and a height of 20 mm, and placed in landfill leachate and soaked for 30 days. The shear strength P0 was then taken out and tested again, and the percentage change in shear strength after treatment λ was calculated according to the following formula;
[0156] λ=[(P0-P1) / P0]×100%
[0157] Wherein, λ-shear strength change percentage, %; P0-initial shear strength of modified mixed soil composition, kPa; P1-shear strength of modified mixed soil composition after impregnation with landfill leachate, kPa; the test results are shown in Table 5;
[0158] Table 5: Statistical table of shear strength data of Examples 10-16 and Comparative Examples 5-10
[0159]
[0160] It can be seen from Table 5 that the modified mixed soil composition prepared by blending the polymer waterproof material prepared in the present application with the modified mixed soil has the advantage of high shear strength, and after being treated with landfill leachate, it still maintains good shear strength.
[0161] It can be seen that the polymer waterproof material prepared in the present application and the modified mixed soil have synergistic effects, and the prepared modified mixed soil composition has the characteristics of high adsorption ratio, fast adsorption rate and selective adsorption, which effectively avoids the problem that after the soil particles are corroded by leachate, the pores between the particles increase, resulting in reduced structural compactness and reduced attraction between particles.
[0162] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.
Claims
1. A polymer waterproof material, characterized in that: The method comprises the following raw materials in parts by weight: 1 part by weight of a modifier, and 3-10 parts by weight of a high molecular polymer; The preparation method of the polymer waterproof material comprises the following steps: mixing a modifier, a solvent and a polymer, reacting for 12-24 hours under stirring at room temperature, washing and drying to obtain the polymer waterproof material; the mass ratio of the modifier, the solvent and the polymer is 1:50-200:3-10, and the solvent is acetone; The preparation method of the modifier comprises the following steps: adding ethylene glycol dimethacrylate, glycidyl methacrylate and polyethylene glycol into a reaction kettle A, adding benzoin dimethyl ether, dispersing evenly, treating with ultraviolet radiation, extracting in a Soxhlet extractor with methanol as solvent, and vacuum drying to obtain the modifier; The method for preparing the high molecular weight polymer comprises the following steps: S1: Add succinic anhydride and diethyltriamine to reaction bottle A and disperse them evenly. Heat to 100-130°C under vacuum conditions and keep warm for 1-3 hours. Heat to 150-170°C and keep warm for 1-3 hours. Add methanol and disperse them evenly. Reprecipitate with acetone, filter, wash and dry to obtain component 1. S2: Add component 1 and anhydrous methanol into reaction bottle B, disperse evenly, heat to 70-80°C, add benzaldehyde, keep warm for 3-6 hours, filter and dry to obtain component 2; S3: Add component 2, N,N-dimethylacetamide and chloroform into reactor B, disperse evenly, let stand at room temperature for 9-12 hours, add 1,2,4-trimellitic anhydride chloride and disperse evenly, continue to add SnCl4, stir for 3-6 hours at room temperature, filter, wash with water and dry to obtain a high molecular polymer.
2. A polymer waterproof material according to claim 1, characterized in that: The mass ratio of ethylene glycol dimethacrylate, glycidyl methacrylate, polyethylene glycol and benzoin dimethyl ether is 1:1.5-3:5-10:0.5-2.
3. A polymer waterproof material according to claim 1, characterized in that: The mass ratio of succinic anhydride, diethyltriamine and methanol in S1 is 1:1-2:5-10.
4. A polymer waterproof material according to claim 1, characterized in that: The mass ratio of component 1, anhydrous methanol and benzaldehyde in S2 is 1:5-10:0.2-0.
5.
5. A polymer waterproof material according to claim 1, characterized in that: The addition ratio of component 2, N,N-dimethylacetamide, chloroform, 1,2,4-trimellitic anhydride chloride, and SnCl4 in S3 is 1g:30-100mL:20-50mL:1-5g:1-2mL.
6. Slope protection waterproof isolation pad, characterized in that: The isolation pad comprises an upper geotextile (1), a lower geotextile (2) and a modified mixed soil composition (3) sandwiched therebetween, wherein the modified mixed soil composition (3) comprises modified mixed soil and the polymer waterproof material described in any one of claims 1 to 5.
7. A slope protection waterproof isolation pad according to claim 6, characterized in that: The preparation method of the modified mixed soil comprises the following steps: after mixing calcium-based bentonite and deionized water evenly, adding tetraethylene pentamine, stirring at room temperature for 1-2 hours, filtering, washing with water until neutral, adding clay, stirring evenly, and obtaining the modified mixed soil; the mass ratio of the calcium-based bentonite, deionized water, tetraethylene pentamine, and clay is 1:10-50:0.1-0.5:8-15.
8. The slope protection waterproof isolation pad according to claim 7 is characterized in that: The modified mixed soil composition (3) is prepared by mixing the modified mixed soil and the polymer waterproof material in a mass ratio of 10:0.5-2.
